Pengaruh Program Kurikulum Merdeka terhadap Pengembangan Kompetensi Pedagogik Guru Penggerak dalam Meningkatkan Mutu Pendidikan di Provinsi Jawa Tengah - Anugrah Perdana; Dhea Fitri Jayanti; Dina Fatmawati; Siswandari Siswandari (Institut Nalanda, 2024)
Abstract. The purpose of this article is to show how the Independent Curriculum program implemented by BBGP Central Java Province has affected the progress of education in Indonesia, especially in improving the quality of teachers. Therefore, teachers must be able to adapt to government regulations in order to achieve national education goals and be able to provide effective and efficient quality learning in encouraging a globally competitive generation, so that teachers must master 4 (four) competencies, namely pedagogical, professional, social and personality. One of the Independent Curriculum programs is teacher mobilization, which is a regional government initiative to strengthen teacher competence and quality through improving pedagogical abilities, leadership and the application of innovation in the learning process. This writing uses a descriptive qualitative method with the data collection techniques used are interviews and literature reviews. The place used for writing this article is the Center for Teacher Mobilization in Central Java Province. The research results show that the entire Merdeka Curriculum program is aimed at improving education in Indonesia, especially the teacher mobilization program which has an important role in improving and increasing the quality of teachers in Central Java. Through BBGP Central Java Province, teachers have the opportunity to take part in training and coaching aimed at improving teaching skills, understanding the latest curriculum, and applying innovative learning methods, so that teachers are able to design learning processes that are relevant to the Merdeka Curriculum, namely learning that emphasizes differentiation, social learning. emotional, and positive discipline.